2009
DOI: 10.1007/s11356-009-0245-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of exhaust gas, liquid products, and residues of printed circuit boards using the pyrolysis process

Abstract: Brominated and chlorinated compounds-i.e., dichloromethane, trans-1,2 dichloroethylene, cis-1,2 dichloroethylene, 1,1,1-trichloroethane, tetrachloromethane, bromophenol, and bromoform-could be high, up to the several parts per million (ppm) level. Low molecular weight volatile organic compounds (VOCs)-i.e., methanol, acetone, ethyl acetate, acrylonitrile, 1-butene, propene, propane, and n-butane-contributed a large fraction of VOCs. The concentrations of toluene, benzene, xylene, ethylbenzene, and styrene were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Dettmer et al observed large amount of BPhs (up to 17%) from thermal degradation of TBBPA. Enhanced BPh levels at 1.3–14.5 mg kg –1 were observed in the pyrolysis of printed circuit boards with a temperature increase from 300 to 500 °C, 2–3 orders of magnitude lower than pyrolysis at 600 °C (1280 mg kg –1 ) but comparable with those at 850 °C (4.7 mg kg –1 ) . These reported results are compatible with the data in the present study.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Dettmer et al observed large amount of BPhs (up to 17%) from thermal degradation of TBBPA. Enhanced BPh levels at 1.3–14.5 mg kg –1 were observed in the pyrolysis of printed circuit boards with a temperature increase from 300 to 500 °C, 2–3 orders of magnitude lower than pyrolysis at 600 °C (1280 mg kg –1 ) but comparable with those at 850 °C (4.7 mg kg –1 ) . These reported results are compatible with the data in the present study.…”
Section: Results and Discussionsupporting
confidence: 92%
“…The significant higher O/I mass ratios of TBBPA from printed circuit boards than from plastic casings also demonstrated that sample matrices and FR-adding types (additive or reactive) can influence on emissions. Reactive TBBPA in printed circuit boards are chemically bonded to the resins, where TBBPA need to be formed from pyrolyzing brominated epoxy resin first in pyrolysis process, and therefore, are less facile to release and subject to less degradation than additive TBBPA and other additive FRs in ABS and HIPS, which are elementary components of plastic casings. Moreover, several O/I mass ratios for HBCD were larger than 1, implicating for potential formation of HBCD from rearrangement of interisomers and unknown sources during treatment processes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chiang et al (Chiang and Lin, 2014;Chiang et al, 2010) carried out the pyrolysis of crushed WCB between 200 and 500 ºC and analyzed the composition of residue, liquid and gaseous fractions. Chien et al (Chien et al, 2000) studied the distribution of Br in pyrolysis products by using a fixed-bed reactor at 350 -800 ºC and thermogravimetry, and found that it mainly evolved as HBr and bromobenzene in the product gas.…”
Section: Introductionmentioning
confidence: 99%
“…), formaldehyde (CH 2 O), glyoxylic acid (C 2 H 2 O), 4,4-methyldiphenol (C 13 H 12 O 2 ), etc. 24 According to the local simulation results, the sources of small molecule pyrolysis products of aromatic amine cured epoxy resin, such as CO In the heating stage, only the cross-linked structure breaks and a small number of macromolecular fragments appear in the pure epoxy resin system. When the system temperature is close to 1700 K, small molecular products begin to appear.…”
Section: Statistics and Analysis Of Main Pyrolysis Productsmentioning
confidence: 99%